2018
DOI: 10.2463/mrms.mp.2016-0113
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating between Central Nervous System Lymphoma and High-grade Glioma Using Dynamic Susceptibility Contrast and Dynamic Contrast-enhanced MR Imaging with Histogram Analysis

Abstract: Purpose:We evaluated the diagnostic performance of histogram analysis of data from a combination of dynamic susceptibility contrast (DSC)-MRI and dynamic contrast-enhanced (DCE)-MRI for quantitative differentiation between central nervous system lymphoma (CNSL) and high-grade glioma (HGG), with the aim of identifying useful perfusion parameters as objective radiological markers for differentiating between them.Methods:Eight lesions with CNSLs and 15 with HGGs who underwent MRI examination, including DCE and DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Average nCBV was the most sensitive parameter in the differential diagnosis of GBMs from PCNSLs and showed the highest AUC in the ROC analysis, with the nCBV of GBM significantly higher than that of PCNSL. This result is consistent with many previous reports, though CBV parameters, such as mean CBV value, 7,18 maximum CBV value, 20,28,43 and 80th percentile of CBV 11 have been shown to be variable. Our results showed that the maximum CBV of PCNSLs tended to be significantly lower than that of GBMs, with a large AUC of 0.848.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Average nCBV was the most sensitive parameter in the differential diagnosis of GBMs from PCNSLs and showed the highest AUC in the ROC analysis, with the nCBV of GBM significantly higher than that of PCNSL. This result is consistent with many previous reports, though CBV parameters, such as mean CBV value, 7,18 maximum CBV value, 20,28,43 and 80th percentile of CBV 11 have been shown to be variable. Our results showed that the maximum CBV of PCNSLs tended to be significantly lower than that of GBMs, with a large AUC of 0.848.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have demonstrated that histogram analyses adapted to CBV or ADC values are superior or comparable to the visually guided ROI-based method for distinguishing tumor type, 11,12,20,30 glioma grading, 21,3133 and recurrence of glioma 3438 and can provide multiple useful parameters in addition to mean and maximum value. Manual ROI methods to evaluate CBV and ADC were highly operator-dependent, and whole-tumor histogram analysis using semi-automatic tumor definition is quantitative and reproducible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraventricular ependymomas are usually in close proximity to the ventricles and contacting them, but the cortically based ependymomas do not contact the ependymal margin at all. However, definitive diagnosis cannot be made with conventional imaging alone [9] , [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%
“…MR perfusion involves dynamic susceptibility contrast (DSC) and dynamic contrast-enhanced techniques that allow for quantification of several tumor parameters, including cerebral blood volume (CBV), cerebral blood flow (CBF), and other contrast-diffusion parameters. [ 17 ] Various studies have suggested the potential use of MR perfusion imaging in the diagnosis of high-grade gliomas,[ 8 ] differentiation of gliomas from lymphomas,[ 12 ] and prediction of tumor aggression and treatment response. [ 1 ] To date, the role of perfusion intraoperative magnetic resonance imaging (iMRI) in the surgical treatment of RELA-fusion positive ependymomas has not been thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%